Activated Charcoal from Coffee Dregs Waste as an Alternative Biosorbent of Cu(II) and Ag(I) - Susy Yunita Prabawati; Priyagung Dhemi Widiakongko; Mohammad Ahsani Taqwim (Universitas Gadjah Mada, 2023)
This study examines the use of coffee dregs waste as biosorbents of Cu(II) and Ag(I). Coffee dregs waste still contains a high level of carbon and cellulose for biosorbents production. The production process was started with charcoal activation using H3PO4. The batch method was applied by variations of contact time, the mass of the biosorbent, and the initial concentration of metal ions. The results showed that Cu(II) and Ag(I) were optimally adsorbed at pH 6 and 4, respectively. The amount of adsorbed metal ions increased with adsorption contact time. The adsorption process of both metal ions reaches stability within 60 min and the optimum biosorbent mass is 1 g. Isothermal adsorption studies show that Cu(II) adsorption tends to follow Langmuir isotherm with an adsorption energy of 31.42 kJ/mol and Ag(I) adsorption follows Freundlich isotherms with an adsorption energy of 27.74 kJ/mol. Based on the results, the interaction between metal ions and adsorbents is a chemical adsorption process and coffee dregs charcoal has the potential to adsorb Cu(II) and Ag(I) metal ions.